Revealing unique inscriptions of a Nazi collaborator in Doodencel 601 of the Oranjehotel - Wempe, Joost; van den Brink, Rick; Mooldijk, Esmée; Feirabend, Nienke; Wiersma, Ruben; Sietsma, Jilt; Dik, Joris (Heritage science, 2020)
During the Second World War the German occupants of the Netherlands made ample use of the Scheveningen prison near The Hague, popularly nicknamed the Oranjehotel . One former death cell in this infamous prison ( Doodencel 601) has been preserved in its original condition, showing wartime inscriptions on the cell walls. Interestingly, a small section of the wall has been given an additional plaster layer, presumably covering inscriptions. Here, we report on the visualization of this enigmatic text, which so far had escaped the reach of historians. Our visualization methodology was threefold. First, we determined the cell-wall stratigraphy and its composition based on a sample cross-section. Second, we prepared a physical model wall, mimicking the layering of the original cell wall. Third, we tested a combination of raking light photography and infrared thermography on the model wall. Applying this methodology on the original wall revealed the inscriptions, including the author’s name Daniël de Blocq van Scheltinga , a prominent Nazi collaborator, as well as a calendar and an important date of his post-war trial in the fall of 1945. Our visualizations flawlessly dovetail with archival findings. Together, they offer an intimate view of an early post-war inmate of the Scheveningen prison, whose message was covered up once the cell was transformed into a war monument in 1946.